Education in the Arab Countries. from the Depth of Centuries to Our Days - Elena V. Koukhareva (Vestnik MGIMO-Universiteta, 2014)
The process of acquiring knowledge and the methods of acquiring it through education and upbringing has a long history in the Arab world. In the pre-Islamic period it meant getting practical skills and relevant knowledge for surviving in the conditions of nomadic life. The main method of transferring knowledge was home education, imitation of the actions of adults and instructions of the elders. The adoption of Islam, at the time of prophet Mohammad, knowledge was presented in the form of divine revelation - Koran. The task of education changed towards learning the scriptures and truths of the new doctrine, spiritual and physical perfection of young people with the aim of their active participation in the spread of Islam. Among the ways of getting an education in that period, along with domestic education and private tutorials, there were two-level religious schools and military training. With the development and strengthening of the Arab Khaliphate, the educational system was perfected and there emerged pedagogical science. The schools of new type - madrasah - taught theological as well as secular subjects. The modern system of education in many Arab countries copies that of their former metropolies. Thus, the system of primary and secondary education in the countries of Maghreb described in the article, was formed under the influence of the French educational system, although in certain cases it takes into account specific national features.